Measuring The Efficiency of Public Spending In Combating Poverty in Indonesia - Prakoso, Muhammad Fajar Dito; Hans, Michael; Wicesa, Nayaka Artha (Jurnal Ekonomi Pembangunan, 2024)
Poverty is a complex issue faced by various countries, including Indonesia. One fiscal instrument in poverty alleviation efforts is the allocation of government public spending. Based on this policy, this research aims to analyze the efficiency of government expenditure in alleviating poverty. This study employs two methods: data envelopment analysis and panel data regression analysis. Government expenditure is proxied by education and health expenditure relative to total government spending. The estimation results of this research indicate that education expenditure has a significant negative effect. Meanwhile, health expenditure has a positive, albeit insignificant, effect on poverty. The contributions of this research include policy recommendations that the government should undertake within its fiscal capacity to address social issues such as poverty.